Effect of IL-27, Teriflunomide and Retinoic Acid and Their Combinations on CD4+ T Regulatory T Cells—An In Vitro Study - Tomasz Maślanka (Molecules, 2022)
The principal goal of the study was to verify the concept of pharmacological induction of Foxp3+CD25+CD4+ T regulatory (Treg) cells which will additionally be characterized by a highly suppressive phenotype, i.e., by extensive CD25 and CD39 expression and IL-10 and TGF-β production. Stimulated and unstimulated murine lymphocytes were exposed to IL-27, teriflunomide (TER), and all trans retinoic acid (ATRA) alone and to their combinations. The study demonstrated that: (a) IL-27 alone induced CD39 expression on Treg cells and the generation of Tr1 cells; (b) TER alone induced Foxp3-expressing CD4+ T cells and up-regulated density of CD25 on these cells; TER also induced the ability of Treg cells to TGF-β production; (c) ATRA alone induced CD39 expression on Treg cells. The experiments revealed a strong superadditive effect between IL-27 and ATRA with respect to increasing CD39 expression on Treg cells. Moreover, IL-27 and ATRA in combination, but not alone, induced the ability of Treg cells to IL-10 production. However, the combination of IL-27, TER, and ATRA did not induce the generation of Treg cell subset with all described above features. This was due to the fact that TER abolished all listed above desired effects induced by IL-27 alone, ATRA alone, and their combination. IL-27 alone, ATRA alone, and their combination affected TER-induced effects to a lesser extent. Therefore, it can be concluded that in the aspect of pharmacological induction of Treg cells with a highly suppressive phenotype, the triple combination treatment with TER, IL-27, and ATRA does not provide any benefits over TER alone or dual combination including IL-27 and ATRA.